2014
DOI: 10.1021/ac5038957
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Analytical Liquid Chromatography Methods for the Characterization of Aqueous Phase from Pyrolysis of Lignocellulosic Biomasses

Abstract: In this work, two analytical liquid chromatography methods were developed and compared for the characterization of aqueous phases from pyrolysis of lignocellulosic biomasses. NanoLC electron ionization-mass spectrometry (EI-MS) represents a novel and useful tool for both separation and identification of semi/nonvolatile and thermolabile molecules. The use of nanoscale flow rates, the highly reproducibility, and high detailed information on EI spectra are the principal advantages of this technique. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 47 publications
1
38
1
Order By: Relevance
“…In view of the complexity of the samples, the comprehensive two-dimensional liquid chromatography (LC × LC) [150] in the same way as it happens for GC × GC becomes an important tool for characterizing bio-oils, because there is a large increase in the resolving power when compared to one-dimensional methods. Another great alternative is the use of micro HPLC columns that allow very small mobile phase flows, facilitating the coupling to more efficient detectors than conventional ones [151][152][153].…”
Section: Analytical Techniques Applied To Bio-oil and Aqueous Phasementioning
confidence: 99%
See 2 more Smart Citations
“…In view of the complexity of the samples, the comprehensive two-dimensional liquid chromatography (LC × LC) [150] in the same way as it happens for GC × GC becomes an important tool for characterizing bio-oils, because there is a large increase in the resolving power when compared to one-dimensional methods. Another great alternative is the use of micro HPLC columns that allow very small mobile phase flows, facilitating the coupling to more efficient detectors than conventional ones [151][152][153].…”
Section: Analytical Techniques Applied To Bio-oil and Aqueous Phasementioning
confidence: 99%
“…Tomasini et al [153] described a method for the characterization of aqueous phases from bio-oils of coconut fiber, sugarcane straw and sugarcane bagasse using comprehensive twodimensional liquid chromatography with detection by diode array followed by mass spectrometry with atmospheric pressure chemical ionization. Using this system, it was identified 26 compounds belonging to the classes of phenols, ketones, furans and alcohols.…”
Section: Two-dimensional Lc (Heart-cutting (Lc-lc)) and Comprehensivementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that RPLC x RPLC had the potential of resolving up to 2000 peaks [7], highlighting the potential of this technique for the comprehensive analysis of the aqueous phase of the bio-oil. Both photo diode array (PDA) and MS detection were latter coupled to RPLC x RPLC and a more detailed analysis could be obtained [8]. Finally, an orthogonal separation system was also recently proposed involving both RPLC and, for the first time, SFC (RPLC x SFC) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of similar columns (e.g., RP-LC×RP-LC) may offer superior resolution [13,14] when different mobile phase pH values [15][16][17] are utilized. This may also be implemented by varying the gradient composition between subsequent 2 D runs [18], according to the properties of the analytes being separated.…”
Section: Introductionmentioning
confidence: 99%